The Correlation Between Learning Motivation And Vocabulary Knowledge And Students' Reading Competence Of The First Grade Students Of SMA Veteran 1 Sukoharjo In The Academic Year 2011-2012 - Palupi, Palupi (2012)
This research was aimed: (1) To find out whether or not learning motivation has a positive correlation with students' reading competence of the first grade students of SMA Veteran 1 Sukoharjo in the academic year 2011-2012. (2) To find out whether or not vocabulary knowledge has a positive correlation with students' reading competence of the first grade students of SMA Veteran 1 Sukoharjo in the academic year 2011-2012. (3) To find out whether or not learning motivation and vocabulary knowledge simultaneously has a positive correlation with students' reading competence of the first grade students of SMA Veteran 1 Sukoharjo in the academic year 2011-2012. This research is a correlational study which studies the correlation between two or more variables or the influence of one variable toward another variable. The research was carried out at SMA Veteran 1 Sukoharjo. The population was the first grade students of SMA Veteran 1 Sukoharjo in the academic year 2011-2012. The samples are 55 students. The data was collected using test and questionnaire. The data was analyzed using multiple linear regression. The research resulted that : (1) There is positive and significant correlation between learning motivation (X1) and reading competence (Y) of the first grade students of SMA Veteran 1 Sukoharjo in the academic year 2011-2012. The value of t observation is greater than the value of t table (3.868> 2.000). (2) There is positive and significant correlation between vocabulary knowledge (X2) and reading competence (Y) of the first grade students of SMA Veteran 1 Sukoharjo in the academic year 2011-2012. The value of t observation is greater than the value of t table (3.672>2.000). (3) There is positive and significant correlation between learning motivation (X1) and vocabulary knowledge (X2) simultaneously and reading competence (Y) of the first grade students of SMA Veteran 1 Sukoharjo in the academic year 2011-2012. The value of F observation is higher than the value of F table (174.604>3.17). Based on the research findings and the conclusions above, the writer suggests students to increase their vocabulary knowledge, to read more and to learn vocabulary through reading. She also suggests students to enhance their learning motivation. She recommends the teacher to enhance students' motivation to learn English by giving incentives, choosing interesting topic, setting and stating the goal of learning, and many other ways.